(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article provides a scholarly analysis of the socio-pedagogical activity of Abdulla Avloni, one of the leading representatives of the Uzbek enlightenment movement in the early twentieth century. The study examines Avloni’s role in establishing Jadid-method schools, modernizing the content of education and moral upbringing, and producing textbooks and methodological materials that contributed to the development of national pedagogical thought. Particular attention is given to his cultural and educational initiatives, including theatrical activities, through which he promoted patriotism, moral maturity, and modern knowledge among the younger generation. Based on Avloni’s work Turkiy Guliston Yohud Akhlok, the article analyzes his views on the unity of education and upbringing, the cultivation of critical thinking, the significance of knowledge and enlightenment in social progress, and the formation of national consciousness. The findings demonstrate that Avloni’s pedagogical legacy remains relevant for contemporary educational practice and theoretical discourse.